1961
DOI: 10.1139/o61-185
|View full text |Cite
|
Sign up to set email alerts
|

Blood Amino Acid Studies: Ii. Effects of Dietary Lysine Concentration, Sex, and Growth Rate on Plasma Free Lysine and Threonine Levels in the Rat

Abstract: Plasma free lysine levels of growing female rats given a lysine-deficient diet supplemented with graded amounts of lysine were higher than those of males. In both sexes, plasma free lysine values rose rapidly in response to added dietary lysine, and reached a maximum at a dietary lysine concentration of approximately 1.0%. This amount of dietary lysine was about 0.2% greater than that found necessary for maximum growth. Male rats given diets containing rapeseed oil and graded amounts of lysine showed reduced g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
25
0

Year Published

1965
1965
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 12 publications
7
25
0
Order By: Relevance
“…The alteration in the plasma amino acid profile observed in this experiment due to the transition from deficiency to adequate lysine supply is in agreement with results reported by others for various amino acids (Morrison et al 1961;Zimmerman and Scott 1965;Brookes et al 1972). The increment of lysine concentration between the lysine-supplemented diets (L2 and L3) and the lysine-deficient diet (L1) was expected because, at low dietary lysine concentra- tions, lysine will be retained intracellularly for preferential channeling into PS rather than to oxidation or to release to the blood circulation.…”
Section: Amino Acidssupporting
confidence: 93%
“…The alteration in the plasma amino acid profile observed in this experiment due to the transition from deficiency to adequate lysine supply is in agreement with results reported by others for various amino acids (Morrison et al 1961;Zimmerman and Scott 1965;Brookes et al 1972). The increment of lysine concentration between the lysine-supplemented diets (L2 and L3) and the lysine-deficient diet (L1) was expected because, at low dietary lysine concentra- tions, lysine will be retained intracellularly for preferential channeling into PS rather than to oxidation or to release to the blood circulation.…”
Section: Amino Acidssupporting
confidence: 93%
“…If a diet is low in a specific amino acid, other amino acids present in the diet are not as completely utilized. This specific amino acid is considered to be a limiting amino acid in the diet (Morrison et al 1961). Knowledge of limiting amino acids is important: supplementation of proper amino acids to a diet increases the nutritional value of the diet as well as the growth rate of the subject; supplemen tation to diet with improper amino acids will be a waste and may result in amino acid imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…This specific amino acid is then a limiting amino acid in this diet (Morrison et al 1961). In this research, the fasting plasma profile equivalent (FPPE) concept Pytelewski 1975, Dubroff et al 1979) was used to determine the order of limiting amino acids.…”
Section: Methodsmentioning
confidence: 99%
“…These phenomena have been recognized by several workers. 26 -30) Gray et al 28 ) and Morrison et al 29 ) reported that the chicks given a lysine-deficient diet had lower levels of free lysine and higher levels of free threonine in the plasma than those given a diet containing adequate amounts of lysine.…”
mentioning
confidence: 99%